Willingness to Pay Premiums for Community-Based Health Insurance in Rural Bangladesh: A Study of Gaibandha District - Dr. Most. Sabiha Sultana; Dr. Tasrun Jahan (Journal of Social Science and Humanities, 2026)
As a signatory of the ‘Alma-Ata Declaration’ in 1978, Bangladesh is committed to ensuring “Health for all,” like many other low- and middle-income countries. Therefore, the study aimed to examine the willingness to pay (WTP) monthly premiums for the community-based health insurance (CBHI) scheme and the factors associated with it, which are crucial for the scheme’s implementation and sustainability before scaling up. A semi-structured questionnaire was used to conduct face-to-face interviews with 516 respondents in the Gaibandha District of northern Bangladesh, selected as the study area. Contingent valuation methods (CVM) with open-ended follow-up questions were employed to identify the WTP for monthly premiums, which ranged from the lowest to BDT 100, 101-200, and above 200 for the CBHI scheme, categorized as “Low,” “Medium,” and “High.” The Proportional Odds Model (POM), a type of ordinal logistic regression (OLR) method, was employed, and the following variables were found to be significant: gender, age, education, occupation, family size, and annual inpatient expenditures. A male-focused premium setting, age-sensitive pricing, occupation-specific strategies, and premium discounts per dependent were suggested in designing the premium rates. Thus, the study provides policy insights into WTP for monthly premiums across various groups and sustainable community-based health financing mechanisms in Bangladesh.